Daytime Lipid Metabolism Modulated by CLOCK Gene Is Linked to Retinal Ganglion Cells Damage in Glaucoma - Denis Gubin; Vladimir Neroev; Tatyana Malishevskaya; Sergey Kolomeichuk; Dietmar Weinert; Natalya Yuzhakova; Alsu Nelaeva; Yulia Filippova; Germaine Cornelissen (Applied Sciences, 2022)
Lipid metabolism is intimately linked to circadian mechanisms and light signaling. Deteriorated photic transduction because of retinal ganglion cell (RGC) loss occurring with glaucoma progression reduces perceived light amplitude, causing circadian disruption. To investigate associations with RGCs, total cholesterol (TC), its low-density (LDL-C) and high-density (HDL-C) fractions, and triglycerides (TG) were measured, under a controlled meal regimen, during daytime hours in 114 patients diagnosed with primary open-angle glaucoma (POAG). RGC damage was assessed by high-definition optical coherence tomography (HD-OCT). Analysis of eight clock, clock-related, and melatonin receptor gene polymorphisms was performed on 19 patients. RGC loss was associated with changes in lipid metabolism in a time-dependent manner. Morning (08:00) values of HDL-C (r = 0.613, p < 0.0001) and TG (r = 0.568, p < 0.0001) correlated positively with RGC global loss, while LDL-C at 08:00 had a weak correlation (r = 0.235; p = 0.012) but showed a strong correlation in the evening (20:00) (r = 0.533, p < 0.0001). The morning–evening gradients (MEGs, changes at 20:00 versus 08:00) in TC and LDL-C changed sign from a negative to a positive association in patients exceeding the 15% two-eye mean GLV threshold. MEG (LDL-C higher in the evening than in the morning) was positive only in POAG patients with the CLOCK_3111 TT genotype.